Socio-demographic Factors Associated with Nutritional Practice during Pregnancy among Pregnant Mothers Attending Federal Tertiary Health Facilities in Ebonyi State, Nigeria - Aleke, Christian O; Ekine, Clarice Siara; Omaka-Amari, Lois N; Obande-Ogbuinya, Nkiru Edith; Emeka, U. Mong; Nwafor, Afoke Eunice; Nwodeh, Raphael Ogbonna; Ohuruogu, Ben N.; Onuenyim, Ngozi; Osuoha, Chinedu Victor; Amanchi , Amina Ogmula (NIGERIAN JOURNAL OF HEALTH PROMOTION, 2024)
Maternal under-nutrition is an emerging public health problem across the world, disproportionately impacting women in developing countries. This study assessed nutritional practice during pregnancy and its associated socio-demographic factors among pregnant mothers attending antenatal clinics at Alex Ekwueme Fetheral Teaching Hospital Abakaliki (AE-FETHA) Ebonyi State. This is a hospital-based study that adopted a cross-sectional survey research design. A self-developed instrument was used to elicit information from the sample of 328 participants. Data analysis was done using frequency, percentage, and multivariate logistic regression at 0.05 alpha level. The findings revealed that 56.7 per cent of the respondents eat food three times in a day, 59.5 per cent eat variety of foods in moderation, 48.5 per cent eat fruit and vegetables occasionally. Moreover, 66.8 per cent are not on any supplement/vitamins, whereas 83.2 per cent do not drink enough water during pregnancy. The multivariate logistic regression adjusted for socio-demographic factors shows that marital status, occupation, and religion are significantly associated with nutritional practice during pregnancy among pregnant women (p≤0 .05). Based on the findings, the study recommended an advanced nutritional education on the important of adequate intake of water, supplement and fruits among mothers during pregnancy. Also using the concerned stakeholders including well-informed religious and traditional leaders to address the socio-demographic factors associated with nutritional practice during pregnancy.